Pola Komunikasi Keluarga Pada Remaja Rantau Selama Masa Perkuliahan - Apriliani, Rasel Silvia; Supratman, Lucy Pujasari (eProceedings of Management, 2024)
Someone who has entered the world of higher education is generally in the late adolescence phase. Issues such aslong- distance communication between parents and college students who have moved away are indeed interesting tostudy because they usually have very close relationships and often communicate directly due to living in the samehousehold. However, due to the decision to move away for the sake of continuing their education, communicationmust be maintained over long distances. This study aims to explain the patterns of family communication amongcollege students who have moved away during their studies. Someone who has entered the world of highereducation is generally in the late adolescence phase. Issues such as long-distance communication between parentsand college students who have moved away are indeed interesting to study because they usually have very closerelationships and often communicate directly due to living in the same household. However, due to the decision tomove away for the sake of continuing their education, communication must be maintained over long distances. Thisstudy aims to explain the patterns of family communication among college students who have moved away duringtheir studies. The results of this study conclude that various approaches are used to maintain a good relationshipwith parents despite being separated by distance. The first student shows awareness of the importance ofmaintaining the quality of the relationship by choosing the right time to talk and committing to maintaining familycloseness. The second student emphasizes the importance of open and honest two-way communication, providingreasons if unable to talk to maintain understanding and balance in the family relationship. The third student takesthe initiative in communication, showing responsibility and readiness to create a harmonious and mutuallysupportive relationship. Overall, these patterns of approach reflect the effective efforts of college students whohave moved away to maintain quality communication with their parents despite being in different locations. Keywords-family communication patterns, college students who have moved away, higher education.